STIMULATIVE RESPONSE TO QUANTITY AND QUALITY OF JOJOBA OIL BY GIBBERELLIC ACID AND BENZYL ADENINE - & et al., Khattab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to evaluate five clones of jojoba plant under the influence of salinity stress which was spraied by gibberellin and benzyl adenine on growth yield and oil. Two field experiments were carried out at Magharah Research and dmting Production which follow Desert Research Center, Agriculture Ministry, in North Sinai governorate, Egypt,  2015/2016 and 2016/2017 respectively, the experimemts wene consist of five clones (S-L, S-610, S- 700, S-B and S-G), (were sprayed by, GA3 200ppm, BA 200ppm and GA3+BA and control) under effect of salinity stress. The experiment was conducted as split plot design having varieties in main plot and IAA, GA3 sub plots three replicates. The jojoba plant was affected by increased GA3, BA or/and GA3+BA, and it was clear in all clones. The effect of GA3, BA or/and GA3+BA varied from one clone to another and the lowest was s-700. All studied variables  were confirmed that clones of jojoba had a significant effect with GA3, BA or/and GA3+BA